2018
DOI: 10.3857/roj.2018.00122
|View full text |Cite|
|
Sign up to set email alerts
|

Intensity-modulated radiation therapy: a review with a physics perspective

Abstract: Intensity-modulated radiation therapy (IMRT) has been considered the most successful development in radiation oncology since the introduction of computed tomography into treatment planning that enabled three-dimensional conformal radiotherapy in 1980s. More than three decades have passed since the concept of inverse planning was first introduced in 1982, and IMRT has become the most important and common modality in radiation therapy. This review will present developments in inverse IMRT treatment planning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 42 publications
0
69
0
5
Order By: Relevance
“…Since IMRT was first performed in 2001 in Korea, implementation of IMRT has been partially covered by national health insurance for specific cancer sites (head and neck, brain, prostate, spinal cancers and re-irradiation cases) from 2011, and since July 2015, the coverage has expanded to include almost all cancers [4]. An abrupt increase from 2015, despite some controversy regarding the cost-effectiveness of IMRT, larger skin dose, and risk of radiation-induced secondary cancers, may have been due to the health insurance coverage and recent advancement in therapeutic machines for IMRT [2,3,7]. The current study showed that the three cancers most frequently treated with IMRT in 2011 were head and neck, prostate, and central nervous system cancers, but in 2018, these were breast, lung, and prostate cancers ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Since IMRT was first performed in 2001 in Korea, implementation of IMRT has been partially covered by national health insurance for specific cancer sites (head and neck, brain, prostate, spinal cancers and re-irradiation cases) from 2011, and since July 2015, the coverage has expanded to include almost all cancers [4]. An abrupt increase from 2015, despite some controversy regarding the cost-effectiveness of IMRT, larger skin dose, and risk of radiation-induced secondary cancers, may have been due to the health insurance coverage and recent advancement in therapeutic machines for IMRT [2,3,7]. The current study showed that the three cancers most frequently treated with IMRT in 2011 were head and neck, prostate, and central nervous system cancers, but in 2018, these were breast, lung, and prostate cancers ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy, along with surgery and chemotherapy, plays a critical role as a main treatment approach for cancer patients [1,2]. Furthermore, radiation therapy trends are shifting from traditional three-dimensional conformal radiation therapy (3DCRT) techniques to complex radiation delivery techniques, such as intensitymodulated radiation therapy (IMRT), volumetric modulated arc therapy (VMAT), and helical tomotherapy (TOMO), all of which deliver more precise and localized dose distributions [3,4]. Because radiation therapy techniques have become more complex and sophisticated, the importance of proper quality control (QC) and quality assurance (QA) for precise patient care has increased [5][6][7], thereby increasing the importance of accurate in vivo and phantom dose measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric modulated arc therapy (VMAT) is an IMRT technique that delivers rotational cone beams with simultaneous modulation of multileaf collimator (MLC) leaves and dose rates [3]. Compared with IMRT which uses fixed gantry angles, VMAT provides an extra degree of freedom, and can reduce treat-ment delivery time and monitor units (MUs) while providing equivalent or improved dose distributions [4,5]. However, because of its complexities in treatment planning and treatment delivery systems, VMAT requires a stringent pretreatment verification to check whether the intended doses will be delivered accurately.…”
Section: Introductionmentioning
confidence: 99%